FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN TBC PARU DI WILAYAH KERJA PUSKESMAS BOLANGITANG - Sabirin B. Syukur; Abdul Wahab Pakaya (program studi ilmu keperawatan fakultas ilmu kesehatan universitas muhammadiyah gorontalo, 2021)
The proportion of patients with smear-positive pulmonary TB in 2012 that 141 people (1:56%) of the total population were found smear-positive and amounted to 130 people (1.44%) of the total population. From the data Bolangitang Health Center in 2012 it is known that there is a population of 9,027 souls 189 (2.09%) were estimated economic suspected pulmonary TB and the suspected when examined totaled 180 people (1.99%). While in 2013 the number of TB patients increased again that 157 people (1:59%) of the total population. Formulation of the problem ie what are the factors associated with the incidence of pulmonary tuberculosis in Puskesmas Bolangitang Mongondow Bolaang North In 2013?. The purpose of the study to determine the factors associated with the incidence of pulmonary tuberculosis in Puskesmas Bolangitang Bolaang North Mongondow. The research design used in this study is the design of the study is descriptive and analytical research methods research is conducted with the main objective to create a picture / relationship about a situation objectively. The survey results revealed that the value of alpha chi square 38.000 with α = 0.000> 0.05 means that there is a relationship between age and the incidence of pulmonary tuberculosis. Chi-square value of 18,661 with a significant level of α = 0.000> 0.05 means that there is a relationship between poverty and the incidence of pulmonary tuberculosis. Chi-square value of 16,765 with a significant level of α = 0.000> 0.05 means that there is a relationship between poverty and the incidence of pulmonary tuberculosis. ased on the results of research and discussion, it can be concluded that age, poverty and the environment associated with the incidence of pulmonary tuberculosis in Puskesmas Bolangitang Bolaang North Mongondow.